Chemical and Biological Amendments and Crop Rotation Affect Soil Carbon and Nitrogen Sequestration by Influencing the Carbon and Nitrogen Contents of Soil Aggregates - Zefang Zhu; Shuangting Li; Kangbo Xu; Jing Wang; Jinfeng Yang; Xiaori Han (Agriculture)
Soil organic carbon (SOC) and total nitrogen (TN) sequestration are vital for maintaining soil fertility and mitigating climate change. This study aimed to evaluate the effects of different amendments (chemical and biological) and crop rotations on SOC, TN sequestration, and soil aggregate distribution. A six-year field study was conducted, involving five different treatments: a monoculture of peanut (PC), a monoculture of maize (MC), a maize-peanut rotation (M-PR), and peanut continuous cropping with chemical (PCCA) and biological (PCBA) amendments. Soil properties, aggregate size distribution, SOC, TN, and enzyme activities were measured. The results show that the bulk density increased, while the field water−holding capacity and porosity decreased with depth. M-PR had the highest macroaggregate (>0.25 mm) proportion, increasing by 21.6–50.8%. SOC and TN increased with aggregate size and were 23.9–103.6% and 7.0–82.9% higher, than PC and MC, respectively, under the treatments. PCCA showed the highest SOC, TN, and enzyme activities. Structural equation modeling indicated that the C and N contents of aggregates directly influenced SOC and TN sequestration. In conclusion, crop rotation and amendments, especially PCCA, effectively improve soil C and N sequestration, and enhance the soil structure, thereby reducing degradation risks, and potentially decreasing on−farm greenhouse gas emissions.